High Viral Load in Upper Respiratory Specimens of Persons With SARS-CoV-2 Infection in a Northern Italian Area. Issue 6 (November 2021) - Valent, Francesca; Mazzilis, Giada; Doimo, Anna; Marzinotto, Stefania; Bulfoni, Michela; Moretti, Valentina; Tullio, Annarita; Curcio, Francesco; Pipan, Corrado
Abstract : Background: An assessment of viral load in biologic specimens of subjects with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may have important implications for public health planning. The aim of this study was to estimate the prevalence of high viral load in upper respiratory specimens of patients with SARS-CoV-2 infection during the first Italian wave (spring) and at the beginning of the second wave (summer) of the COVID-19 epidemic, through the measurement of cycle threshold (Ct) values from real-time reverse transcription-polymerase chain reaction tests conducted at the University Hospital of Udine, Italy, serving 530, 000 inhabitants. Methods: We compared the prevalence of high viral load, defined as Ct ⩽ 20 at the first positive test result, in 262 subjects from the spring and 453 from the summer period. Logistic regression was used to account for potential confounding due to sex, age, and severity of infection. Results: In the spring, 9.2% of subjects had Ct ⩽ 20 versus 21.4% in the summer. After adjusting for confounders, the likelihood of having high viral load was 2.9 times higher in the summer than in the spring (95% confidence interval, 1.7–5.0). Conclusions: In this Italian area, more COVID-19 patients had high viral load in the spring epidemic wave than at the beginning of the second, during the summer. Cycle threshold values may represent useful information to monitor viral load at a population level in subjects with SARS-CoV-2 infection.